Age and vascular aging: an unexplored frontier - González, Laura del Mar; Romero-Orjuela, Sara P.; Rabeya, Fernando J.; del Castillo, Valeria; Echeverri, Darío (Frontiers in Cardiovascular Medicine, 2023)
Vascular age is an emerging field in cardiovascular risk assessment. This concept includes multifactorial changes in the arterial wall, with arterial stiffness as its most relevant manifestation, leading to increased arterial pressure and pulsatile flow in the organs. Today, the approved test for measuring vascular age is pulse wave velocity, which has been proven to be a predictor of cardiovascular events. Furthermore, vascular phenotypes have been found, like early vascular aging and -SUPERNOVA,‖ which are phenotypic extremes of vascular aging, and whose identification opens a new field of study in cardiovascular physiology. Lifestyle interventions and pharmacological therapy have been shown to positively affect vascular health, reducing arterial stiffness. This review aims to define the concepts related to vascular age, pathophysiology, measurement methods, clinical signs and symptoms, and treatment.